2007
DOI: 10.1007/s12134-007-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Career Nomadism and the Building of a Professional Identity in Female Immigrants

Abstract: This article paints a picture of the professional integration of female immigrants in the Quebec City area, a city in which they are a small minority. Our main interest is the obstacles to their socio-professional integration. We attempt to shed light on this reality by giving an overview of the effects that disruptions in a woman's career in general and an immigrant woman's career in particular have in that, as workers in the so-called secondary sector, they are often the first affected by market polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…Importantly, it considered activities outside of paid labour not as separate from it but as directly influenced by it. A handful of studies have documented racialized immigrant women's multiple and often concurrent strategies in response to underemployment and precariousness, both in the labour market (Ng et al 2006;Cardu 2007;McCoy and Masuch 2007) and in the household (Creese, Dyck, and McLaren 2008). Our study adds to this literature by documenting how under/unemployment, experienced at the individual and household levels, resulted in the intensification of job search activities and of the household/caregiving work, which carried their own risks for health.…”
Section: Discussionmentioning
confidence: 64%
“…Importantly, it considered activities outside of paid labour not as separate from it but as directly influenced by it. A handful of studies have documented racialized immigrant women's multiple and often concurrent strategies in response to underemployment and precariousness, both in the labour market (Ng et al 2006;Cardu 2007;McCoy and Masuch 2007) and in the household (Creese, Dyck, and McLaren 2008). Our study adds to this literature by documenting how under/unemployment, experienced at the individual and household levels, resulted in the intensification of job search activities and of the household/caregiving work, which carried their own risks for health.…”
Section: Discussionmentioning
confidence: 64%
“…The same applies to work experience abroad' (Schuster, Desiderio & Urso 2013, p. 18). Research has also indicated how lack of relevant social capital contributes to the underemployment and deskilling of migrants (Morrice, 2007;Cardu, 2007). In her study of female migrants, Cardu lists a number of reasons including lack of knowledge of the labour market (where to go, how to make skills known, how to access internships), and lack of networks to help them familiarise themselves with the work culture, such as how to behave during a job interview (Cardu, 2007).…”
Section: Situating Learning In the Social Worldmentioning
confidence: 99%
“…Although immigrants to Canada do improve their economic standing over time, this has been less pronounced for recent cohorts –scholars now question whether today’s immigrants will ever entirely “catch up” (Frenette and Morissette, 2003; Green and Worswick, 2004; Aydemir and Skuterud, 2005). While the assimilation perspective suggests that early jobs will lead to better employment over time, qualitative research on the Canadian experiences of skilled immigrants portrays such jobs as dead ends (Man, 2004; Cardu, 2007). The low‐level jobs in which many labor not only lack promotion possibilities, but also limit immigrants’ time to invest in education or training and lead to the atrophy of important higher‐level work skills (Pratt, 1999; McCoy and Masuch, 2007).…”
Section: Immigrant Labor Market Trajectoriesmentioning
confidence: 99%